Energy prices, environmental policies and investment Evidence from listed firms - Dlugosch, Dennis (OECD Publishing, 2017)
The 2°C (or less) limit on global warming agreed at the UN Climate Change Conference of 2015 in Paris effectively implies that manufacturing industries in developed countries have to undertake significant investments, in particular in more energy efficient production technology. To implement policies making the most of such a change, policymakers need to know what consequences climate policies have on business investment. This paper sheds light on the relationship between environmental policies, energy prices and firm-level investment using a sample of listed firms over the period 1995-2011 in 30 OECD economies. Higher energy price inflation is associated with a small, but statistically significant decrease in total investment across firms, though in the most energy intensive sectors, total investments are actually found to increase. However, for domestic investment, effects of higher energy price inflation are negative, independent of the energy intensity of industries. The gap in reactions between total and domestic investment is likely driven by increased offshoring in response to higher energy price inflation, in line with the Pollution Haven Hypothesis. We also find tentative evidence that the negative effects of rising energy prices on investment can be largely attributed to tightening upstream environmental policies
Keywords: Economics